2011
DOI: 10.1007/s10641-010-9765-z
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use, feeding and territorial behavior of a Brazilian endemic damselfish Stegastes rocasensis (Actinopterygii: Pomacentridae)

Abstract: This paper presents the results of the first field study of the Brazilian endemic damselfish Stegastes rocasensis. Underwater data were collected at the Fernando de Noronha Archipelago (NE Brazil), where four sites were visually assayed for local territorial and feeding behaviors, as well as habitat use. S. rocasensis preferentially fed on turf and macroalgae, and during the afternoon period. Its territory size ranged from 0.26 to 13.86 m 2 (1.61± 0.23 m 2 ). Our findings suggest that adults preferably inhabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 55 publications
0
16
2
Order By: Relevance
“…Based only on morphological criteria, S. rocasensis and S. sanctipauli have been considered similar to each other and to S. variabilis Castelnau 1855 [22,27]. Although scarce biological information is available [14,28,29], there is some genetic data or information on its evolutionary history [23,30,31]. In order to clarify the taxonomic status and relationships of these three insular species and test the current hypotheses of ancestrality [22,27], counts comparisons of serial elements, traditional and geometric multivariate morphometric analyses, and analyses of mitochondrial (16S ribosomal RNA-16S, cytochrome oxidase subunit 1-COI, and cytochrome B-CytB) and nuclear gene sequences (nuclear recombination-activating gene 1-rag1 and rhodopsin-rhod) were performed.…”
Section: Open Accessmentioning
confidence: 99%
“…Based only on morphological criteria, S. rocasensis and S. sanctipauli have been considered similar to each other and to S. variabilis Castelnau 1855 [22,27]. Although scarce biological information is available [14,28,29], there is some genetic data or information on its evolutionary history [23,30,31]. In order to clarify the taxonomic status and relationships of these three insular species and test the current hypotheses of ancestrality [22,27], counts comparisons of serial elements, traditional and geometric multivariate morphometric analyses, and analyses of mitochondrial (16S ribosomal RNA-16S, cytochrome oxidase subunit 1-COI, and cytochrome B-CytB) and nuclear gene sequences (nuclear recombination-activating gene 1-rag1 and rhodopsin-rhod) were performed.…”
Section: Open Accessmentioning
confidence: 99%
“…The exceptions among the top most abundant species at FN are Stegastes rocasensis and Malacoctenus aff. triangulatus, endemics to Atol da Rocas (AR) and FN, where they occurs in a wide range of depths and hydrodynamic regimes (Rosa and Moura 1997;Floeter et al 2001, Souza et al 2011.…”
Section: General Patterns Of Community Structurementioning
confidence: 99%
“…In a more detailed study of the distribution of S. rocasensis at FN, Souza et al (2011) sampled four sites (Porto, Boldró, Conceição and Sancho) and found that adult individuals preferably inhabit shallow areas, while sub-adults and juveniles occupy deeper areas with lower wave exposure. The greater abundance of adults in shallower areas was hypothesised to be related to their stronger territorial behaviour, which resulted in their permanence within their territory even during "adverse situations", such as low tides and high wave impact (Souza et al 2011). Even with the probable resistance of some adult individuals of S. rocasensis to these adverse situations, we noticed that this species may avoid some very shallow places.…”
Section: Relationships Of Fish Density and Biomass And Environmental mentioning
confidence: 99%
“…Use of space within a home range may be partitioned among a variety of activities, such as foraging, reproduction and resting (Eristhee & Oxenford 2001, Claisse et al 2011. Although variations in the home ranges of fish have been linked to a series of factors, such as body size (Jones 2005), habitat composition (Chapman & Kramer 2000) and fish abundance (Mumby & Wabnitz 2002), the use of space by fish when they are actively foraging has not been comprehensively explored, although some work has looked at foraging movements in smaller, territorial species, particularly damselfish (Souza et al 2011). As a result, variation in foraging ranges and the driving mechanisms for these variations are poorly understood.…”
mentioning
confidence: 99%